2005
DOI: 10.1002/jmri.20363
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of lesion volume in acute stroke treated by intravenous t‐PA

Abstract: Purpose:To determine the evolution of the ischemic lesion volumes in a population treated with tissue plasminogen activator (t-PA), MRIs were performed before treatment and 24 hours later; final infarct size was evaluated 60 days later. Materials and Methods:A total of 42 patients with hemispheric stroke were recruited for a thrombolytic study. Intravenous t-PA was given after MRI within the first seven hours after stroke onset. Volumes were evaluated on day 0 and day 1 with diffusion-weighted imaging (DWI), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…8 Volume changes with tPA treatment have been studied by others. 2,4,15,16 Not all investigators, however, found volume decrease after tPA treatment. For example, Röther et al found that median 7-day T2 volumes were larger than the baseline DWI (35 mL versus 22 mL) among 76 patients treated with intravenous tPA within 6 hours of onset of symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…8 Volume changes with tPA treatment have been studied by others. 2,4,15,16 Not all investigators, however, found volume decrease after tPA treatment. For example, Röther et al found that median 7-day T2 volumes were larger than the baseline DWI (35 mL versus 22 mL) among 76 patients treated with intravenous tPA within 6 hours of onset of symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment strategies show great variations in different hospitals regarding the method (intra-arterial versus intravenous procedures) and time window for eligibility. Al- though recanalization may favor partial reversibility of the DWI anomaly, 24 the baseline brain stem DWI score may help to identify patients most likely to benefit from treatment. Extensive brain stem damage may indicate poor prognosis regardless of recanalization success or failure (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…Median baseline DWI and PWI lesion volumes were 42 cm 3 (interquartile range, 3 to 108 cm 3 ) and 188 cm 3 (interquartile range 60 to 252 cm 3 ), respectively. The mean change in DWI lesions on follow-up MRI was 38.46Ϯ50.4 cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The extent of DWI lesion enlargement has been correlated with final infarct size and long-term clinical outcome. [3][4][5][6] Therefore, DWI lesion growth has been proposed as a surrogate outcome measure in neuroprotective and thrombolytic trials. 7,8 This idea is supported by the demonstration that DWI abnormality growth may be attenuated or even reversed, partially or completely, after early therapeutically driven recanalization.…”
mentioning
confidence: 99%